2012
DOI: 10.1039/c2sm26311d
|View full text |Cite
|
Sign up to set email alerts
|

Two component gels of immiscible blends of biscarbamates (polyurethane model compounds) and poly(ε-caprolactone)

Abstract: We describe the gelation of two-component immiscible blends consisting of a set of low molecular weight organogelators and a polymer. We studied the blends of poly(3-caprolactone) (PCL) and biscarbamates (model compounds for polyurethanes) with two hydrogen bonding motifs separated by a (CH 2 ) 6 spacer and symmetrically attached alkyl side chains. Neither PCL nor the biscarbamates form gels with chloroform in their neat forms, although the latter form gels with several other solvents. It is known that PCL doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Another case of a small molecule organic gelator leading the polymer gelation was reported by Khan et al These authors have studied the crystallization and gelation characteristics of biscarbamates, with various alkyl side chain lengths . These are model compounds for polyurethanes (PU).…”
Section: Small Molecule/polymer Organo Gelsmentioning
confidence: 99%
“…Another case of a small molecule organic gelator leading the polymer gelation was reported by Khan et al These authors have studied the crystallization and gelation characteristics of biscarbamates, with various alkyl side chain lengths . These are model compounds for polyurethanes (PU).…”
Section: Small Molecule/polymer Organo Gelsmentioning
confidence: 99%
“…They would self‐sort irrespective of the way they were crystallized. In an earlier study, we found that biscarbamates did not form gels with chloroform. Poly(ϵ‐caprolactone) (PCL) by itself is not known to gel any solvent.…”
Section: Discussionmentioning
confidence: 82%
“…Our studies on melt‐crystallization of these molecules showed that the rates of crystallization and spherulite growth to be maximum with a C 8 or C 9 side chain. On the basis of simple energy calculations, we showed that a balance between the hydrogen bond and van der Waals interaction energies occurs with side chain lengths of C 8 or C 9 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations